Synthesis, in silico and in vitro antimicrobial activity of N-(benzyl)-5-methyl-4-oxo-3,4-dihydrothieno[2,3-d]pyrimidine-6-carboxamides - Sergiy V. Vlasov; Oleksandr V. Borysov; Hanna I. Severina; Vitaliy S. Vlasov; Amjad Ibrahim M. Abu Sharkh; Victoriya A. Georgiyants (Pensoft Publishers, 2024)
According to the recent studies bezylcarboxamide fragment attached to the thiophene ring of thieno[2,3-d]pyrimidine is beneficial for antimicrobial activity of the compounds. Therefore we focused our efforts on constructing of the simple molecules such as N-(benzyl)-5-methyl-4-oxo-3,4-dihydrothieno[2,3-d]pyrimidine-6-carboxamides to get deeper insight into their antimicrobial activity. As the optimal procedure for preparation of target compounds we choose 1,1'-carbonyldiimidazole promoted interaction of 5-methyl-4-oxo-3,4-dihydrothieno[2,3-d]pyrimidine-6-carboxylic acid with the series of substituted benzyl amines. The obtained amides showed good activity against the strains of S. aureus and B. subtilis, which was higher for the derivative without substituents in benzene ring or the compounds with small substituents like methyl or methoxyl groups in the para-position of the benzene ring. Docking studies showed that despite the good values of the scoring functions, the conformational analysis of the ligands' poses in the active site revealed their ability for only partial inhibition of TrmD of P. aeruginosa.